Pencitraan Lingkungan Dengan Virtual Reality Photography - Ranang Agung S (Institut Seni Indonesia Surakarta, 2007)
This art works research entitled: â€œEnvironment Imaging by Virtual Reality Photographyâ€ aims to obtain an appropriate technique to take a 360 degree photography and to get a photography that can image the environment virtually, so that it can be developed in advanced application as an interactive visual element and to be appealing in interactive CD or website.This study was conducted in the form of technological experimentation and image technique in virtual reality manner. The result of research shows that the photography making of VR panorama requires the good mastery of photography technique through proper engineering of photography equipment and various photography technical experiments and digital imaging mastery and image developing by multimedia authoring technology, particularly with Virtual Reality software. And the VR panorama photography can create a more comprehensive environment because in its enjoyment it involves hands, eyes and even ears, hence creating the integration of physical, immersive and enjoyable activities.Keywords: Imaging, Environment, Virtual, Reality, Photography